OLAH VOKAL DALAM TARI INDANG PARIAMAN SUMATRA BARAT (Kajian tekstual dan fungsi) - Efrida Efrida (Institut Seni Indonesia Surakarta, 2012)
Indang is one of traditional arts which develops in Pariaman, West Sumatra. This traditional art is a combination of literature and dance movements. This research aims to find out the textual and functional changes developing in accordance with the society’s taste. The data was collected through observation, interviews, and literary study. The data was analyzed using an analysis on textual and functional changes. The research result showed that the vocal of Indang dance existed in small Muslim chapels accompanied by songs containing Islamic lyrics. The indang dance had changed from a sacred into a profane dance. That the movements of Indang dance are relatively simple and monotonous but the dance keeps on existing is interesting. The Islamic teaching in the lyric of oral literature always complies with the society’s taste. Indang dance functions as entertainment and a means of communication performed for a variety of purposes. Key words : indang, textual, changes, function, Pariaman Pengantar